Extração da pectina do maracujá amarelo (Passiflora edulis f. flavicarpa) para incorporação em biofilmes - Lima, Rodrigo Tanajura Freire Meira (2019)
The yellow passion fruit (Passiflora edulis f. Flavicarpa) is a fruit produced and exported in abundance by Brazil, widely used in the food industry to produce juices and pulps. After the production stage, the husks and seeds, which correspond to about 75% of the fruit, are not usually harvested and discarded or used as animal feed. These portions of the fruit could be used as feedstock to obtain products with higher added value, such as extracting the oil from the seeds, or pectin from the bark. In the present work, passion fruit peels were used to extract pectin in acidified medium with citric acid in the following conditions of temperature, pH and extraction time: 95 °C, 2 and for 90 minutes. The pectin yield ranged from 5.35% to 21.88% and the degree of esterification ranged from 21.11% to 70%. The high degree of pectin obtained was used as biopolymer for the production of biofilms combined with glycerol by the technique of Solvent Casting. Biofilms were produced that were evaluated for their thickness, humidity, solubility, mechanical properties and visual characteristics.